2016
DOI: 10.1007/s12017-016-8398-6
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals in Parkinson’s Disease

Abstract: Current pharmacological strategies for Parkinson’s disease (PD), the most common neurological movement disorder worldwide, are predominantly symptom relieving and are often plagued with undesirable side effects after prolonged treatment. Despite this, they remain as the mainstay treatment for PD due to the lack of better alternatives. Nutraceuticals are compounds derived from natural food sources that have certain therapeutic value and the advent of which has opened doors to the use of alternative strategies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 136 publications
1
27
0
Order By: Relevance
“…However, these opposite effects were sustained by similar pathogenetic mechanisms as they were both counteracted upon antioxidant (EGCG) administration [ 28 , 65 ], consistent with the hypothesis that FA is to be primarily considered as a disorder of the oxidative metabolism [ 11 , 12 , 22 , 41 ]. In addition, this is also consistent with the protective effects of antioxidant treatment against tissue damage, demonstrated in distinct neurodegenerative disorders including Parkinson disease [ 70 , 71 ], Alzheimer Disease [ 72 ], as well as some forms of dementia [ 51 , 73 , 74 , 75 , 76 ].…”
Section: Discussionsupporting
confidence: 83%
“…However, these opposite effects were sustained by similar pathogenetic mechanisms as they were both counteracted upon antioxidant (EGCG) administration [ 28 , 65 ], consistent with the hypothesis that FA is to be primarily considered as a disorder of the oxidative metabolism [ 11 , 12 , 22 , 41 ]. In addition, this is also consistent with the protective effects of antioxidant treatment against tissue damage, demonstrated in distinct neurodegenerative disorders including Parkinson disease [ 70 , 71 ], Alzheimer Disease [ 72 ], as well as some forms of dementia [ 51 , 73 , 74 , 75 , 76 ].…”
Section: Discussionsupporting
confidence: 83%
“…Note, however, that at least one mushroom trial indicated no measurable benefits in healthy young physical education students (514) . Brain and serum ERG levels are also markedly different in Parkinson's disease (515) , reviewed in Hang et al (516) , Shao & Le (517) and Shah & Duda (518) , and even in sudden infant death syndrome (519) , and ERG has been shown to be protective against β-amyloid-induced neuronal injury (520) and cytotoxicity (521) . It can also act as an antidepressant (522) .…”
Section: Neurological Diseases and Cognitive Functionmentioning
confidence: 99%
“…In light of the above-mentioned evidence on the crucial role of ROS in the pathogenesis of PD, anti-ROS therapy has been an attractive strategy to counteract the oxidative stress-induced neuronal cell death in PD [ 87 ]. Classic antioxidants mainly include vitamin C, vitamin E, Coenzyme Q10 (CoQ10), GSH, NAC, and creatine.…”
Section: Anti-ros With Compounds For the Therapeutics Of Pdmentioning
confidence: 99%